Pengaruh Komisaris Independen, Capital Intensity Dan Financial Distress Terhadap Konservatisme Akuntansi - Putri, Lestari; Sari, Intan Rahma (Jurnal Ekonomika Dan Bisnis (JEBS), 2024)
This research aims to test and prove the influence of independent commissioners, capital intensity and financial distress on accounting conservatism” (Empirical Study on LQ 45 index companies listed on the BEI for the 2018-2023 period).The type of research used is a quantitative method. The type of data used is secondary data in the form of financial reports of LQ 45 companies listed on the Indonesia Stock Exchange for the period 2018-2023. Samples were collected using the purposive sampling method. The number of companies that met the research sample criteria was 15 companies out of 45 companies with a research period of 6 years of observation, so that a total of 90 research samples were obtained. Data processing using the Eviews 10 Statistical Program. Next, carrying out various tests including descriptive statistical tests, panel data model tests, model selection tests, classical assumption tests and hypothesis tests. So the research results prove that independent commissioners, capital intensity and financial distress simultaneously influence accounting conservatism. Independent commissioners partially influence accounting conservatism. capital intensity influences accounting conservatism. Financial distress has no effect on accounting conservatism.